Strategi Pemberdayaan Masyarakat untuk Mengatasi Stunting dan Mewujudkan Generasi Unggul di Kabupaten Tanah Laut - Safira, Bella; Jauharah, Jauharah; Maulida, Sri; Ikrimah, Ikrimah; Qoshid Al Hadi, M. (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Indonesia is a developing country where the incidence of stunting is quite high. Where South Kalimantan is in the 5th highest position out of 20 provinces in Indonesia with the incidence of stunting reaching 44.2% in the previous year. Tanah Laut Regency as a whole accounts for around 24.6% of stunting incidents, so this condition is very worrying for several groups, for this reason, MAB Kalimantan Islamic University KKN students went directly to the field to provide education about preventing stunting in children. A descriptive analysis was carried out on the knowledge of mothers who had received counseling by asking them directly in the form of interviews about what things they could implement in preventing stunting based on the delivery of education during counseling. Apart from that, it describes the influence of the results of maternal blood pressure checks on the chances of stunting due to anemia or hypertension in children. The results of blood pressure checks in Hamlet 2 in Handil Birayang Atas, Tanah Laut show the risk of anemia in mothers as the main cause of stunting in the area. Knowledge about nutritious food is a factor that can trigger anemia and have an impact on the health of the next generation